ANALISIS PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY, PROFITABILITAS, DAN LEVERAGE TERHADAP MANAJEMEN PAJAK - Anugrah, Surya; Yuliana, Christina (BALANCE: Jurnal Akuntansi, Auditing dan Keuangan, 2020)
This research is conducted to analyze the influence of disclosure of Corporate Social Responsibility, profitability, and leverage to tax management. The company must pay taxes to the government as one of the stakeholders. On the other hand, the company is also required to perform its social responsibility as an effort to gain legitimacy from the local community. The study was conducted on manufacturing companies listed in the Indonesia Stock Exchange from 2013 to 2015 and by using the panel data analysis method. Of the 143 companies, 70 companies meet population requirements. The number of samples used in this research amounted to 168 units of observation. The data used in this study is secondary data obtained from financial reports and annual reports. The results show that the variables of Corporate Social Responsibility Disclosure, profitability, and leverage effect to tax management.